Immigrant health: Selectivity and acculturation - Guillermina Jass; Douglas S. Massey (Institute for Fiscal Studies (IFS), 2004)
There is renewed concern that in spite of overall improvements in health racial and ethnic disparities in health persist and in some cases may even have expanded. Ethnic health disparities are inherently linked to immigration since ethnic identities are traced to the country of origin of an immigrant or his ancestors. The average healthiness of the original immigrants, the diversity in health status among immigrants, the subsequent health trajectories following immigration both over immigrants lifetime and that of their descendents all combine to produce the ethnic health disparities we observe at any point in time. Identifying the determinants of the original health selection of migrants and the forces that shape health paths following immigration is critical to understanding ethnic health differences.
Keywords: 330; Gesundheit; Ethnische Gruppe; Großbritannien; Migranten